Hidden pictures [large type] - Rekulak, Jason (Thorndike Press large print mystery series., 2022)
"Mallory Quinn takes a job as a babysitter for Ted and Caroline Maxwell. She bonds with Teddy, a sweet, shy boy who is never without his sketchbook and pencil. His drawings are the usual fare: trees, rabbits, balloons. But one day, he draws a man dragging a woman's lifeless body. Then, Teddy's artwork becomes more and more sinister, and his stick figures quickly evolve into lifelike sketches well beyond the ability of any five-year-old. Mallory begins to wonder if these are glimpses of a long-unsolved murder, perhaps relayed by a supernatural force. Knowing how crazy it sounds, Mallory sets out to decipher the images and save Teddy before it's too late"--